A Feasibility Study Investigating a Topical Preparation as Novel Adjunct Treatment for the Symptomatic Management of Vulvovaginal Skin Conditions - Philip Hall (Mary Ann Liebert, 2024)
Objective: The study aimed to investigate the feasibility of a newly available topical gel in improving the symptoms of various vulvovaginal skin conditions (NCT05396261). Methods: Fifty-two women with diagnosed lichen sclerosus, lichen simplex chronicus, or genitourinary syndrome of menopause participated in this prospective single-arm feasibility study. Consented patients applied the product daily internally and externally to the genital area for approximately 6 months (short-term) and optionally up to 2 years (long-term). Outcome measures included patient-rated symptoms, investigator-assessed clinical signs, and visual severity of pathology of these vulvovaginal conditions. Clinical outcomes, patient adherence to the treatment, and adverse events were assessed, and the statistical analysis was split according to short-term and long-term treatment. Results: The majority of patients enrolled in the study suffered from an uncontrolled disease (90.4%). All patients showed significant improvement in all patient-rated symptoms (p < 0.001), overall clinical signs (p < 0.001), and visual severity of pathology (p < 0.001) short-term. These favorable results were maintained from month 6 up to 2 years. Patient compliance was high, and no adverse events were reported with use of the investigational product. Conclusions: This topical medical device could be an effective symptomatic management option for women suffering from various vulvovaginal conditions.